Black Boxes: Flat Worlds, Automated Subjects, and the Air France 447 Disaster. - Rollason, Will (Social Analysis, 2025)
When Air France flight 447 was lost in the Atlantic in 2009, stories about the disaster were initially set in the real space of the sky and ocean. Journalists and investigators searched for clues to a reality hidden in the depths of the sea. After the discovery of the aircraft's 'black box' flight recorders two years later, the volumes that had governed earlier narratives were replaced by network imagery spreading over a flat plane. This article explores the agency of the flight recorders in producing this narrative shift. It uses that insight to argue that the conceptual spaces of contemporary life may have a patchy quality, and thus that social scientific methodologies based on network imagery may not be universally applicable.